EDUKASI PERBANKAN SYARIAH KEPADA GENERASI ZILENIAL - Yessi Nesneri; Irdayanti Irdayanti; Anna Nurlita; Aras Aira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Islamic banking is one of the Islamic financial services that has an important role in driving the pace of the economy. Islamic banking education for the zilenial generation aims to increase knowledge about Islamic banking, especially the zilenial generation who think that Islamic banking is only for adults. The method of implementing this activity uses the Participatory Action Research (PAR) method. The results of this activity indicate that there has been an increase in knowledge about Islamic banking among the educational participants and many are interested in using Islamic banking in everyday financial transactions.Keywords: Islamic Banking, Islamic Banking Education, Zilenial Generation